Tính tổng S=9x11+99x101+999x1001+9999x10001+99999x100001
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
A = 1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101
6A = 6 x (1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101)
6A = 1 x 3 x 6 + 5 x 7 x 6 + 9 x 11 x 6 + ... + 99 x 101 x 6
6A = 1 x 3 x (5 + 1) + 3 x 5 x (7 - 1) + 5 x 7 x (9 - 3) + ⋯ + 99 x 101 x (103 - 97)
6A = 1 x 3 x 1 + 1 x 3 x 5 + 3 x 5 x 7 - 1 x 3 x 5 + 5 x 7 x 9 - 3 x 5 x 7 + ⋯ + 99 x 101 x 103 - 97 x 99 x 101
6A = 1 x 3 x 1 + (1 x 3 x 5) + (3 x 5 x 7) - (1 x 3 x 5) + (5 x 7 x 9 ) - (3 x 5 x 7) + ⋯ + (99 x 101 x 103) - (97 x 99 x 101)
6A = 3 - 99 x 101 x 103 = 1019703
=> A = 1019703/6
A = 1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101
6A = 6 x (1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101)
6A = 1 x 3 x 6 + 5 x 7 x 6 + 9 x 11 x 6 + ... + 99 x 101 x 6
6A = 1 x 3 x (5 + 1) + 3 x 5 x (7 - 1) + 5 x 7 x (9 - 3) + ⋯ + 99 x 101 x (103 - 97)
6A = 1 x 3 x 1 + 1 x 3 x 5 + 3 x 5 x 7 - 1 x 3 x 5 + 5 x 7 x 9 - 3 x 5 x 7 + ⋯ + 99 x 101 x 103 - 97 x 99 x 101
6A = 1 x 3 x 1 + (1 x 3 x 5) + (3 x 5 x 7) - (1 x 3 x 5) + (5 x 7 x 9 ) - (3 x 5 x 7) + ⋯ + (99 x 101 x 103) - (97 x 99 x 101)
6A = 3 - 99 x 101 x 103 = 1019703
=> A = 1019703/6
2/(7 × 9) + 2/(9 × 11) + 2/(11 × 13) + ... + 2/(97 × 99)
= 1/7 - 1/9 + 1/9 - 1/11 + 1/11 - 1/13 + ... + 1/97 - 1/99
= 1/7 - 1/99
= 92/693
A = 1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101
6A = 6 x (1 x 3 + 5 x 7 + 9 x 11 + ... + 99 x 101)
6A = 1 x 3 x 6 + 5 x 7 x 6 + 9 x 11 x 6 + ... + 99 x 101 x 6
6A = 1 x 3 x (5 + 1) + 3 x 5 x (7 - 1) + 5 x 7 x (9 - 3) + ⋯ + 99 x 101 x (103 - 97)
6A = 1 x 3 x 1 + 1 x 3 x 5 + 3 x 5 x 7 - 1 x 3 x 5 + 5 x 7 x 9 - 3 x 5 x 7 + ⋯ + 99 x 101 x 103 - 97 x 99 x 101
6A = 1 x 3 x 1 + (1 x 3 x 5) + (3 x 5 x 7) - (1 x 3 x 5) + (5 x 7 x 9 ) - (3 x 5 x 7) + ⋯ + (99 x 101 x 103) - (97 x 99 x 101)
6A = 3 - 99 x 101 x 103 = 1019703
=> A = 1019703/6
\(\frac{4}{5.7}+\frac{4}{7.9}+\frac{4}{9.11}+...+\frac{4}{99.101}\)
\(=2.\left(\frac{2}{5.7}+\frac{2}{7.9}+\frac{2}{9.11}+...+\frac{2}{99.101}\right)\)
\(=2.\left(\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+\frac{1}{9}-\frac{1}{11}+...+\frac{1}{99}-\frac{1}{101}\right)\)
\(=2.\left(\frac{1}{5}-\frac{1}{101}\right)\)
\(=2.\frac{96}{505}\)
\(=\frac{192}{505}\)
\(\frac{4}{5.7}+\frac{4}{7.9}+...+\frac{4}{99.101}\)
\(=2.\left(\frac{2}{5.7}+\frac{2}{7.9}+...+\frac{2}{99.101}\right)\)
\(=2.\left(\frac{1}{5}-\frac{1}{7}+\frac{1}{7}-\frac{1}{9}+...+\frac{1}{99}-\frac{1}{101}\right)\)
\(=2.\left(\frac{1}{5}-\frac{1}{101}\right)\)
\(=2.\left(\frac{101}{505}-\frac{5}{505}\right)\)
\(=2.\frac{96}{505}\)
\(=\frac{192}{505}\)
Chúc bạn học tốt !!!